Effect of Wheat RING Type E3 Ligase TaMARCH9 Gene on Flowering Time in Transgenic Arabidopsis - Moon Seok Kim; Jae Ho Kim; Yong Weon Seo (Plant breeding and biotechnology, 2022)
Grain yield in wheat is mostly governed prior to flowering during primordia development. Mature primordia development, floret fertility, and maximum grain number per spikelet are the three most important characteristics of spike development. The genes involved in primordia formation, on the other hand, have remained unclear. Here, we demonstrate molecular characterization of Triticum aestivum MARCH9 (TraesCS7A01G283700) which encodes RING domain, might play a positively regulating primordium and floret development until anthesis stages. TaMARCH9 expression level was highly induced at differentiation stages (WS 3-6) in Yeongkwang cultivar. TaMARCH9 exhibited ubiquitination activities and was localized to the plasma membrane using a transient expression system in tobacco. Moreover, overexpression of TaMARCH9 in Arabidopsis plant displayed early flowering phenotypes compared to wild-type. Some of flowering related genes such as FLC, MAF, FT and SOC were highly induced in TaMARCH9- overexpressing Arabidopsis plants. Our finding suggested that TaMARCH9 may act a key role in the formation of floret primordium development and/or flowering time in wheat.